Initiation of four basal insulins and subsequent treatment modification in people treated for type 2 diabetes in the United Kingdom: Changes over the period 2003–2018. Issue 8 (31st May 2021) - Brunetti, Vanessa C.; Yu, Oriana H. Y.; Platt, Robert W.; Filion, Kristian B.
Abstract: Aims: Aim of this study is to describe changes in the utilization of basal insulins (glargine, detemir, degludec, neutral protamine Hagedorn [NPH]) among individuals with type 2 diabetes between 2003 and 2018 in the United Kingdom (UK). Materials and Methods: Using the UK Clinical Practice Research Datalink (CPRD) Aurum, we created three study cohorts of individuals with type 2 diabetes: (1) all users of antidiabetic drugs ( n  = 686, 170); (2) initiators of antidiabetic drugs ( n  = 382, 247); and (3) initiators of basal insulins ( n  = 85, 369). Trends in prescription rates were determined using Poisson regression overall and stratified by sex, cardiovascular disease history, and obesity. Crude and adjusted Cox proportional hazards models were used to obtain hazard ratios (HRs) and confidence intervals (CI) comparing rates of treatment change between classes of basal insulins, with an intention‐to‐treat exposure definition. Results: During the study period, prescription rates of insulin analogues increased in the all‐user cohort from 118.3 (95% CI: 116.4, 120.2) prescriptions per 1000 person‐years in 2003 to 579.4 (95% CI: 576.9, 582.0) in 2018. Prescription rates of NPH decreased from 770.5 (95% CI: 765.0, 775.3) in 2003 to 457.7 (95% CI: 455.5, 460.0) in 2018. Compared to initiators of NPH, initiators of detemir were more likely to change treatment (adjusted HR: 1.31, 95% CI: 1.25, 1.37) while glargine initiators were less likely to change treatment (adjusted HR: 0.85, 95% CI: 0.82, 0.88). Conclusions: Basal insulin prescription evolved between 2003 and 2018. Our study provides insight into the evolving use of basal insulin among individuals with type 2 diabetes in the UK.